SYST-15 TARGETING AXONAL GUIDANCE WITH ANTI-ROBO1 CAR T CELLS: A NEW THERAPEUTIC STRATEGY FOR MALIGNANT BRAIN CANCER. (5th August 2022) - Brakel, Benjamin; Chokshi, Chirayu; Rossotti, Martin; Venugopal, Chitra; Salim, Sabra; Mobilio, Daniel; Chafe, Shawn; Henry, Kevin; Singh, Sheila
Abstract: No standardized treatments exist for patients with treatment-refractory brain metastasis, glioblastoma and other recurrent brain tumours. Given the aggressive nature of these diseases and difficulty in modelling tumour recurrence, minimal efforts have been made to design rational therapies against them. Neurodevelopmental pathways are often highjacked and go awry in the progression of these cancers. The roundabout guidance receptor 1 (ROBO1) protein is involved in axonal guidance during neurodevelopment, and we have shown that aberrant ROBO signalling promotes invasiveness and tumour growth in glioblastoma. Likewise, this signalling may contribute to the metastasis and growth of metastatic brain tumours, making the ROBO1-expressing tumour cell population an attractive and functionally relevant therapeutic target. Here, we present that ROBO1 is highly expressed on the surface of malignant and treatment-refractory brain tumour initiating cells (BTICs), prompting the development of an anti-ROBO1 CAR-T cell therapy. Using the binding region of a single-domain antibody targeting ROBO1, we developed second-generation anti-ROBO1 CAR-T cells specific and effective against malignant brain cancers, upregulating markers of activation and degranulation upon exposure to ROBO1-expressing BTICs. Additionally, orthotopic patient-derived xenograft models of malignant brain tumours treated with anti-ROBO1 CAR-T cells had a reduced tumour burden and prolonged survival, demonstrating therapeutic potential for treating brain malignancies.